Femminile e maschile nel Settecento - Passetti, Cristina; Tufano, Lucio (Biblioteca di storia, 2018)
In the 18th century, the relationship between the male and the female became particularly relevant and turned into an excellent test bench within the construction process of the individual's identity. Many are the images connected to the genre. Likewise, the self-representation processes through which the subjects read, describe and project themselves in their own existential context are complex and articulated. Twenty-three essays on different disciplines (history, literature, philosophy, figurative arts, science, music and theatre) explore the eighteenth-century dialectics between the two principles, using updated and specific methodological approaches. From the whole of the investigations, a complex picture with its ambiguities emerges. In it, he categorisations are continually renegotiated both in terms of intellectual elaborations and social practices.